The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.4025/actascianimsci.v34i4.15055
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of beef cattle and the microclimate with and without shade

Abstract: ABSTRACT. It was evaluated the intake behavior of Nellore steers in system without shade (WS), and silvopastoral system (SP) maintained in star grass (Cynodon plectostachyus) in summer and winter. Twentyfour Nellore steers were used (12 in each system), mean age 18 months and weight of 294.5 kg. The design was completely randomized with two seasons, two treatments, 24 hours and 12 repetitions. The observations were conducted in three days, for 24 hours, with an interval of 15 minutes, with effect of the hour o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 16 publications
0
7
0
2
Order By: Relevance
“…For cattle, the main benefit due to the presence of trees is undoubtedly the improvement of environmental conditions and consequently their welfare (Porfírio da Silva 2009). According to Baliscei (2012), changes in temperature, radiation incidence, and humidity are directly related to their thermal comfort. Pires et al (2010) emphasized that changes in grazing and rumination patterns, excessive dislocation, and frequent water intake can be signs of heat stress.…”
Section: Introductionmentioning
confidence: 99%
“…For cattle, the main benefit due to the presence of trees is undoubtedly the improvement of environmental conditions and consequently their welfare (Porfírio da Silva 2009). According to Baliscei (2012), changes in temperature, radiation incidence, and humidity are directly related to their thermal comfort. Pires et al (2010) emphasized that changes in grazing and rumination patterns, excessive dislocation, and frequent water intake can be signs of heat stress.…”
Section: Introductionmentioning
confidence: 99%
“…Grazing activity and milk production The higher grazing time in OP was most likely explained by the lower CP content of herbage, which was compensated by selective grazing by the animals and thus longer grazing duration (Olivo et al, 2006;Baliscei et al, 2012). The results indicated that higher idling time in the SPS may reflect benefits from the shade of trees during daylight.…”
Section: Nutritive Valuementioning
confidence: 95%
“…Animals' body temperature is determinant to their thermal comfort (Baliscei et al 2012), productivity and reproductive efficiency (Garcia et al 2010). Baliscei et al (2013) measured black globe temperature, which is strongly correlated with animals' body temperature, and found lower values in silvopastoral system than in an open area.…”
Section: Potential Use Of Silvopastoral Systems To Attenuate Climate mentioning
confidence: 99%
“…For animals, thermal stress occurs when air temperature reaches values higher than the thermoneutral range (Armstrong 1994). Such condition causes increase of animals' body temperature, which is determinant to their thermal comfort (Baliscei et al 2012), which affects productivity and reproductive efficiency (Garcia et al 2010). As consequences of such stress, physiological and behavior adaptations occur, like preference for shaded places, increases of water intake, peripheral vasodilation, sweating, and respiratory rate (Blackshow and Blackshow 1994), and, as consequence, reduction of animal productivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation